UNRAVELLING THE VISION OF PEACE AND UNITY A CRITICAL DISCOURSE ANALYSIS OF JOHN LENNON’S IMAGINE - Jaelani, Alan; Nuraeni, Nuraeni; Perdana Prasetya, Eska; Juraboev, Sarvar; Ayu Fadhilah, Annisa; Dwi Rizky, Indah; Monalisa, Monalisa (ENGLISH JOURNAL, 2023)
This research investigates the iconic and timeless masterpiece song "Imagine" by John Lennon, seeking to unravel the profound messages and ideologies that lie beneath its evocative lyrics for peace, unity, and social change. The study employs Critical Discourse Analysis (CDA) by Teun A. van Dijk to conduct a comprehensive analysis of macrostructure, superstructure, and microstructure of the song. This research adopts a qualitative approach, utilizing content analysis and thematic analysis to explore the meanings and messages conveyed in the lyrics. Content analysis is employed to examine the explicit messages and themes presented in the song, while thematic analysis delves into the implicit meanings and underlying ideologies. This study finds that in the level of macrostructure, the vision of a utopian world free from religious, national, and materialistic barriers emerges as the central message, emphasizing the value and dignity of every individual. The superstructure analysis delves into the construction of the song’s elements and their cohesive arrangement, highlighting its universal appeal and global consciousness to participate actively in creating positive change to build a better world. The microstructure analysis investigates the nuanced meanings conveyed by specific linguistic elements, such as rhetorical devices, lexical choices, emotive language, and direct address. Beyond its explicit messages, "Imagine" serves as a critique of societal constructs that perpetuate divisions and inequalities, challenging listeners to imagine alternative ways of organizing society based on compassion and shared humanity.